Factors associated with stress, anxiety and depression in nursing professionals in the hospital context - Bianca Bacelar de Assis; Cissa Azevedo; Caroline de Castro Moura; Patrick Gonçalves Mendes; Larissa Lucas Rocha; Aline Alves Roncalli; Nayara Ferreira Mota Vieira; Tânia Couto Machado Chianca (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to determine the factors associated with stress, anxiety and depression, concomitantly, in nursing professionals who work in the hospital context. Methods: a quantitative and cross-sectional study with 353 nursing professionals from a hospital. A sociodemographic questionnaire and the Depression, Anxiety and Stress Scale-21 were used. Data were subjected to descriptive statistical analysis, difference and correlation tests. Results: the main factors associated with stress, anxiety and depression, concomitantly, were being female, compromised family and social support, lack of autonomy at work, hostile relationship with colleagues, lack of professional recognition and satisfaction, feeling of being overwhelmed and insecurity. Conclusions: demographic, physiological, social and work factors impact the levels of stress, anxiety and depression in nursing professionals. The adoption of coping strategies for modifiable factors should be considered, in order to provide better quality of life for these professionals.